Assessment of solar energy potential in Johor, Malaysia - Samsudin, Muhammad Zahid; Didane, Djamal Hissein; Elshayeb, Said A.; Manshoor, Bukhari (FAZ Publishing, 2021)
Solar energy is one of the well-known renewable energy sources from sunlight that convert to free-pollution energy. One of the major development problems for developing countries is the energy dilemma. The energy problem is considered a significant obstacle to economic development. In the current situation, solar energy can be considered one of the safest options. This paper presents the assessment of solar energy potentials at nine stations in Johor, Malaysia for a five-year period stretching between 2015 and 2020. The assessment data for all stations were obtained from the Malaysian meteorological department. The meteorological parameters involved include temperature, extraterrestrial solar radiation and clearness index. The assessment technique involved the use of the Angstrom-Prescott (A-P) model to estimate the solar energy potentials at the sites. From the results obtained from the A-P model, it is apparent that Station Segamat has the highest average monthly global solar radiation on the horizontal surface with 6.7921 kWh/m2 monthly solar radiation, while Pontian station has the lowest with 6.7893 kWh/m2 monthly solar radiation. The monthly clearness index throughout the year in each station varies between 0.65 to 0.7 and the maximum temperature ranges from 22.71°C at Pontian station to 32.42°C at station Kota Tinggi. Based on the comparison and analysis of the results, it is clear that each station at Johor has an excellent solar energy potential and is suitable for photovoltaic module system application.